Effect of air flow on liquid water transport through a hydrophobic gas diffusion layer of a polymer electrolyte membrane fuel cell - Suresh, P.V.; Jayanti, S. (International journal of hydrogen energy, 2010)
The transport of liquid water through an idealized 2-D reconstructed gas diffusion layer (GDL) of a polymer electrolyte membrane (PEM) fuel cell is computed subject to hydrophobic boundary condition at the fibre–fluid interface. The effect of air flow, as would occur in parallel/serpentine/interdigitated type of flow fields, on the liquid water transport through the GDL, ejection into the channel in the form of water droplets and subsequent removal of the droplets has been simulated. Results show that typically water flow through the fibrous GDL occurs through a fingering and channelling type of mechanism. The presence of cross-flow of air has an effect both on the path created within the GDL and on the ejection of water into the channel in the form of droplets. A faster rate of liquid water evacuation through the GDL (i.e., more frequent ejection of water droplets) as well as less flooding of the void space results from the presence of cross-flow. These results agree qualitatively with experimental observations reported in the literature.